Allelopathic potential of cover crops in control of shrubby false buttonweed (Spermacoce verticillata). - VARGAS, L. A. (2018)
Searching for alternatives to deal with weeds without the exclusive use of herbicides can increase the sustainability of agricultural production in the Amazon region. This study aimed to evaluate the allelopathic potential of cover crops on the weed shrubby false buttonweed (Spermacoce verticillata L.). Three straw levels (1; 2.5 and 5 mg cm-2) of thirteen cover crops (Cajanus cajan, Canavalia ensiformis, Crotalaria juncea, C. ochroleuca, C. spectabilis, Mucuna aterrima, M. cinereum, Pennisetum glaucum, Sorghum bicolor, S. sudanense, Urochloa brizanha cv. Xaraés, U. brizantha cv. Piatã and U. ruziziensis) were assessed on germination and initial growth of weed and lettuce. We carried out two experiments (weed and lettuce) in a factorial scheme (cover crops x straw levels) with additional treatment (control without straw) in a completely randomized experimental design, with four replicates. The straw of the cover crops inhibited the germination and initial growth of the target plants. The highest straw levels promoted 44.0 and 78.8% reductions in radicle length in relation to the lowest dose (1 mg cm-2), for lettuce and Spermacoce verticillata, respectively. The highest sensitivity to allelochemicals occurred on the radicle. The major suppressive effects on weed germination were promoted by Cajanus cajan, Urochloa brizanha cv. Xaraés, Mucuna cinereum, M. aterrima, Canavalia ensiformis, Crotalaria juncea, C. spectabilis and U. ruziziensis. Cover crops use is an integrated practice management to control Spermacoce verticillata under no-tillage system.